Forecasting Number of Covid-19 Positive Patients in Sorong City Using the Moving Average and Exponential Smoothing Methods - Matheus Supriyanto Rumetna; Tirsa Ninia Lina (STMIK Budi Darma, 2021)
Sorong City is a part of West Papua Province, Indonesia. This city is one of the cities which have been affected by the Covid-19. This research attempts to provide a solution for the Sorong City Covid-19 Task Force’s need for forecasting number of potential Covid-19 positive patients in the coming months so that faster treatment could be made. Such need has emerged due to the absence of laboratories and the increasing number of positive Covid-19 patients in the city. The absence of laboratories in the city has made the task force to send samples of presumed Covid-19 patients to the laboratories in Makassar City in order to be examined and tested. This process has been time consuming and further reducing the task force’s already reduced performance effectiveness because of the social distancing policy applied in cities in Indonesia. The forecasting methods utilized in the research were the Moving Average and Exponential Smoothing. The methods were applied using POM-QM Software for Windows Version 5. The results of the Exponential Smoothing method are better than the results of the Moving Average method in forecasting the number of possible Covid-19 patients in July. For August and September forecasts, the results of the Moving Average method are better than the results of the Exponential Smoothing method. The results from both methods could be used as reference by the Sorong City Covid-19 Task Force in making decision and establishing policy.